ANALISIS SWOT UJIAN NASIONAL BERBASIS KOMPUTER - Pernamawati, Suryanita; Kristiawan, Muhammad; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2021)
This study was to know SWOT Analysis of a Computer-Based National Examination at the State Senior High School 1 of Tanjung Raja. The research was qualitative. The data collected by questionnaire, and documentation. Data were analyzed by SWOT analysis. From the results of the study it can be concluded that the SWOT analysis of the main strength factors possessed by State Senior High School 1 of Tanjung Raja was the basic abilities, interests and high motivation of student learning, supported by the qualifications of teacher education in accordance with the subject teacher's diploma, So that student achievement in the implementation of UNBK is sufficient satisfying. While the weakness is the ability to understand students' UNBK questions is still not optimal. The opportunity by State Senior High School 1 of Tanjung Raja in the implementation of UNBK was support by the goverment in Implementation of UNBK. While the threat is that the curriculum created by the government often experiences changes.